Population features of Boeckella poppei in Lake Wujka, King George Island - V. Trokhymets; V. Gorobchyshyn; I. Kozeretska (Ukrainian Antarctic Journal, 2021)
The maritime Antarctic is one of the most interesting regions on planet where climate change can be observed to impact all components of its poor flora. Boeckella poppei is common in the maritime and continental Antarctic species of the copepod. The aim of the study was to check the local trends in the copepod's population density over summer. The samples were collected 23.12.05, 03.01.06 and 10.01.06 at the King George Island from the lake near the Polish Antarctic Station. The population density varied with strongly fluctuating ratios of different juvenile and generative developmental stages. We also analyzed the regularities reported by other authors. The sex structure of the population did not change during the study period with females much more numerous than males. The article discusses possible causes of this phenomenon.